2016
DOI: 10.4038/tare.v17i2.5309
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, screening and in vitro evaluation of bacterial antago-nists from spent mushroom substrate against Colletotrichum musae

Abstract: Colletotrichum musae is a major pathogen in banana fruit which causes heavy losses at the postharvest stage. As a viable alternative to harmful chemical usage and physical control measures, the potential of using bacterial antagonist against C. musae was evaluated in this study. Out of a total of 92 bacterial isolates derived from dilution plates of aqueous extracts of spent mushroom substrate (SMS), 43 isolates were initially selected for screening for antagonistic activity against the C. musae isolate CMK01.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The pathogen C. musae was isolated from naturally infected banana fruit which is brought from Dhule fruit market showing typical symptoms circular to angular / irregular ring, light to dark brown spots with a dark red or blackish margin were used to isolate the pathogen by tissue segment method [18] on potato dextrose agar (PDA) medium. Further, the seven days old culture of C. musae were used for the in vitro efficacy of bioagents and fungicides test.…”
Section: Source Of Pathogenmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogen C. musae was isolated from naturally infected banana fruit which is brought from Dhule fruit market showing typical symptoms circular to angular / irregular ring, light to dark brown spots with a dark red or blackish margin were used to isolate the pathogen by tissue segment method [18] on potato dextrose agar (PDA) medium. Further, the seven days old culture of C. musae were used for the in vitro efficacy of bioagents and fungicides test.…”
Section: Source Of Pathogenmentioning
confidence: 99%
“…in culture media. Costa and Subasinghe[30,31,18] observed the effect of P. fluorescens on the C. musae. The results regarding the effect of bio agents are also agreements with the many plant pathologists, [32] who also reported that T. harzianum and T. viride were shown to be the most effective in vitro condition against C. gloeosporioides.…”
mentioning
confidence: 99%
“…), which affects both mature and damaged green fruits. Additionally, banana tip rot, crown rot, and blossom end rot have all been caused by C. musae [21,[22][23][24]. The disease typically develops during extended periods of storage and transit that are characterized by low temperatures and high humidity.…”
Section: Introductionmentioning
confidence: 99%
“…Spent mushroom substrate can control plant diseases through several mechanisms. The efficacy of spent mushroom compost has been related to the activity of microorganisms that are antagonistic to plant pathogens [7,[10][11][12]. Spent mushroom substrates also contain antimicrobial substances that inhibit pathogen growth [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…lycopersici [11] and Rhizoctonia solani [12]. Bacterial isolates from spent oyster mushroom substrate were also effective at inhibiting the growth of plant pathogens in vitro, including Colletotrichum musae [10], and Fusarium solani [16].…”
Section: Introductionmentioning
confidence: 99%